International Court of Justice and municipal courts : an inter-judicial dialogue - Kuc, Oktawian (Routledge research in international law., 2022)
"Recent decades have brought international and municipal courts much closer together and induced meaningful cooperation. This holds true also for the International Court of Justice and domestic judicial institutions as they engage actively in an inter-judicial dialogue, particularly on the normative level. Due to the impact of globalisation and internationalisation, the World Court has expanded its jurisprudence to also accommodate references and analysis of external judicial organs and their pronouncements. Likewise, ICJ decisions are referred to and consulted by municipal courts as authoritative statements of international norms or assistance in fact determination. This monograph examines this inter-judicial dialogue in a comprehensive manner by identifying and analysing all its aspects as evidenced in respective jurisprudence"--Publisher's description.